A analysis of the contents and use of B. P. S. Form 178 by elementary school supervisors in the Division of Pangasinan - Aquino, Gaudencio V. 1924- (s.n.], 1965)
This is an analysis of the contents and use of B.P.S. Form 178 by elementary school supervisors in the division of Pangasinan during the school year 1962-1963. The study also investigated the objectives of the supervisors in using this form and the problems encountered by instructors in accomplishing this form.